First record of Adeonellopsis subsulcata (Smitt, 1873) (Bryozoa: Gymnolaemata) in Cuba - Sosa-Yañez, Armando (2014)
Adeonellopsis subsulcata (Smitt, 1873) (Bryozoa: Gymnolaemata) was first reported in Cuba on the marine terraces of the “Desembarco del Granma” National Park at the southeastern Cuban coast. Samples were collected using SCUBA gear at 12 m (19º 49’ 48’’ N, 77º 39’ 11’’ W) and 14 m deep (19º 50’ 04’’ N, 77º 42’ 34’’ W). Reference material has been included in the zoological collections of the Cuban Center for Coastal Ecosystems Research (Centro de Investigaciones de Ecosistemas Costeros-CIEC).